Flexible Metal Oxide/Graphene Oxide Hybrid Neuromorphic Transistors on Flexible Conducting Graphene Substrates. Issue 28 (9th May 2016) - Wan, Chang Jin; Liu, Yang Hui; Feng, Ping; Wang, Wei; Zhu, Li Qiang; Liu, Zhao Ping; Shi, Yi; Wan, Qing
Abstract : Flexible metal oxide/graphene oxide hybrid multi‐gate neuromorphic transistors are fabricated on flexible conducting graphene substrates. Dendritic integrations in both spatial and temporal modes are emulated, and spatiotemporal correlated logics are obtained. A proof‐of‐principle visual system model for emulating Lobula Giant Motion Detector neuron is also investigated. The results are of great significance for flexible sensors and neuromorphic cognitive systems.